The Concept and Role of Culture in Socioscientific Systems - Masudul Alam Choudhury (International Institute of Islamic Thought, 1998)
The term “culture” has two interesting connotations in social thought. Both carry important implications on the kind of social interrelationships that are generated by the preferences formed at the level of the individual. Since culture is an intermediate course for generating interrelationships, which in turn reinforce and continue the very meaning of culture, a cause-effect relationship must exist between social transformation and culture. In this, the formative basis of culture, the individual and groups must play a determining role. Such a social-political-institutional approach to the study of culture, though not prevalent in common literature, has played a central role in two opposing schools. The first school was generated from Ibn Khaldun’s concept of the “science of culture.”’ The second was given life by the ontological status given to culture by Hegel in his definition of the “world spirit,” which he associated with the heart of western civilization.2 (Weber, too, saw in culture the same characteristic?) These two perspectives have recently been invoked by Fukuyama to expound his own theory of the “end of hi~tory.”H~e sees the Hegelian dialectical process to be at the heart of an atomism of culture- the “isothymia,” as he calls it-and governing individualism. When viewed in light of a transmitting medium for social change against the perspectives of different worldviews, the role of culture has been construed in terms of “cultural pluralism.” But when this is taken up in the light of its transforming and cause-effect impact on social transformation, cultural pluralism is nothing less than the consequence of a particular political philosophy. Thus, an important causal nexus of “global” interactions emerges: First, there is a worldview that establishes a meaning of culture. Second, the meaning of culture so formed creates a ...